2006
DOI: 10.1557/proc-932-17.1
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Sorption in a Sedimentary rock/saline Groundwater System and Spectroscopic Evidence

Abstract: Sorption of selenium (Se) was studied by batch technique by using sedimentary rock samples andcorresponding saline groundwater from Horonobe underground research laboratory (URL)site under reducing condition. Spectroscopic analyses were performed by X-ray absorption near-edge structure (XANES) afterthe sorption experiments to identify the oxidation states of Se on the sedimentary rock. It issuggested thatthe dominant parameters affecting the Se sorption are iron-bearing minerals, especially exchangeable Fe and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Naveau et al 31) and Breynaert et al 32) reported that the sorption mechanism of Se(IV) onto pyrite was a redox reaction with sulfur but not iron, supporting the interpretation by Xia et al 15) and Liu et al 30) Although it is not clarified whether Se can be incorporated into pyrite, it seems not to occur easily because the crystalline system of ferroselite (FeSe 2 ; orthorhombic) is different from that of pyrite (FeS 2 ; cubic). 20) Thus, the sorption mechanism of selenide onto pyrite is probably a local redox reaction with sulfur at the surface, as shown in Eq.…”
Section: Sorption Behavior Onto Mineral Samplesmentioning
confidence: 65%
See 4 more Smart Citations
“…Naveau et al 31) and Breynaert et al 32) reported that the sorption mechanism of Se(IV) onto pyrite was a redox reaction with sulfur but not iron, supporting the interpretation by Xia et al 15) and Liu et al 30) Although it is not clarified whether Se can be incorporated into pyrite, it seems not to occur easily because the crystalline system of ferroselite (FeSe 2 ; orthorhombic) is different from that of pyrite (FeS 2 ; cubic). 20) Thus, the sorption mechanism of selenide onto pyrite is probably a local redox reaction with sulfur at the surface, as shown in Eq.…”
Section: Sorption Behavior Onto Mineral Samplesmentioning
confidence: 65%
“…The K d values obtained for sandy mudstone were compared to previously reported ones for mudstone and shale 10,[14][15][16] (Fig. 8).…”
Section: Sorption Behavior Onto Rock Samples (1) Granodioritementioning
confidence: 87%
See 3 more Smart Citations